Author Correction: A novel quantitative PCR mediated by high-fidelity DNA polymerase - Mengling Zhang (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.